Usefulness of PCR for Trypanosoma cruzi DNA in blood and endomyocardial biopsies for detection of Chagas disease reactivation after heart transplantation: A comparative study. Issue 4 (2nd February 2021) - Benvenuti, Luiz A.; Freitas, Vera L. T.; Roggério, Alessandra; Nishiya, Anna S.; Mangini, Sandrigo; Strabelli, Tânia M. V.
Abstract: Background: Chagas disease reactivation (CDR) after heart transplantation is characterized by relapse of the infectious disease with proliferation and dissemination of Trypanosoma cruzi parasites. Serial blood PCR testing is consensually recommended for CDR monitoring, but there is uncertainty about the incremental value in performing the molecular tests in endomyocardial biopsies (EMB). Methods: We compared qualitative and quantitative results of PCR for T cruzi DNA in 62 pairs of blood and EMB collected with a maximum time interval of 7 days, from 34 heart‐transplanted, chagasic patients. Results: Blood PCR resulted positive in 39/62 (62.9%) samples, with PL ranging from 0.14 to 1610.73 (median: 3.31). PCR resulted positive in 8/60 (13.3%) EMB, with PL ranging from 2.82 to 1670.55 (median: 65.63). All blood samples which tested negative presented a paired EMB which also tested negative. However, 31/39 (79.5%) blood samples which tested positive presented a paired EMB which tested negative. There was poor agreement between blood and EMB PCR (kappa = 0.153). CDR affecting the myocardium (myo‐CDR) was diagnosed in three occasions. PCR resulted positive in both blood and EMB at the time of myo‐CDR, with PL ranging from 0.61 to 1610.73 in blood and 13.8 to 1670.55 in EMB. Conclusions: Negative PCR for T cruzi in blood rules out myo‐CDR, with no value of testing EMB. Positive PCR in blood with high PL is diagnostic for myo‐CDR. If PCR in blood results positive with low PL, testing EMB is useful: negative PCR turns unlikely, and positive PCR reinforces greatly the possibility of myo‐CDR.